MicroRNA-153 inhibits osteosarcoma cells proliferation and invasion by targeting TGF-β2. - Guangfeng Niu; Bin Li; Li Sun; Chenggong An (PLoS ONE, 2015)
Increasing evidence indicates that microRNAs (miRNAs), a class of small noncoding RNAs, participate in almost every step of cellular processes. MiRNAs are aberrantly expressed in human cancers and contribute to cancer development and progression. Study of miRNAs may provide a new clue for understanding the mechanism of carcinogenesis and a new tool for cancer treatment. In the present study, miR-153 was downregulated in human osteosarcoma tissues and cell lines. Introduction of miR-153 mimics into the MG-63 cells inhibited cell proliferation and invasion. Our results further revealed that transforming growth factor beta 2 (TGF-β2) was negatively regulated by miR-153. Furthermore, overexpression of miR-153 decreased p-SMAD2, p-SMAD3, epidermal growth factor receptor (EGFR) and insulin-like growth factor binding protein-3 (IGFBP-3) expressions, which were the downstream signaling molecules of TGF-β. Furthermore, miRNA-153 suppressed TGF-β-mediated MG-63 proliferation and migration. Therefore, our results suggest that miR-153 may act as a tumor suppressor in osteosarcoma through targeting TGF-β2.